2012
DOI: 10.1186/1475-9276-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ views on factors that contribute to health care inequalities among immigrants in Sweden: a qualitative study

Abstract: IntroductionEthnic and socioeconomic inequalities in the Swedish health care system have increased. Most indicators suggest that immigrants have significantly poorer health than native Swedes. The purpose of this study was to explore the views of midwives on the factors that contribute to health care inequality among immigrants.MethodsData were collected via semi-structured interviews with ten midwives. These were transcribed and related categories identified through content analysis.ResultsThe interview data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 34 publications
4
72
1
6
Order By: Relevance
“…The findings in our study are in the line with other studies which showed that some participants could not access information because they were unfamiliar with the structure of the Swedish healthcare system. Lacking linguistic skills and difficulties in communication with care providers, for example regarding information about their disease and involvement in treatment, caused frustration and increased the risk of misunderstandings, miscommunication and inequalities in healthcare provision (27,28,29). All of the informants belonged to the same cultural-geographical area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in our study are in the line with other studies which showed that some participants could not access information because they were unfamiliar with the structure of the Swedish healthcare system. Lacking linguistic skills and difficulties in communication with care providers, for example regarding information about their disease and involvement in treatment, caused frustration and increased the risk of misunderstandings, miscommunication and inequalities in healthcare provision (27,28,29). All of the informants belonged to the same cultural-geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies about the healthcare system among refugees showed that immigrants in Sweden have significantly poorer health than native Swedes (17). And may therefore have increased need for healthcare services (18,19).Previous studies made in Sweden about refugees coming from Burundi, Colombia, Iraq, Kazakhstan, Poland, Kosovo and Syria, showed that the main problems were related to feelings of being uninformed and being sent to various levels of care, which resulted in lack of trust, and feelings that no one took overall responsibility (20).…”
Section: Doi: 105455/msm20142685-89mentioning
confidence: 99%
“…Assim como alguns estudos já realizados (Tobin, Lawless, 2014;Akhavan, 2012), as barreiras na linguagem foram identificadas como um desafio para a assistência às mulheres imigrantes. Na fala da enfermeira obstetra Maria, podemos entender como ela tenta se comunicar com uma paciente em trabalho de parto:…”
Section: As Dificuldades Encontradas Na Assistência àS Mulheres Imigrunclassified
“…No estudo de Akhavan (2012), a linguagem foi um instrumento fundamental para promover uma comunicação eficaz, onde as enfermeiras relatam que seria muito melhor se a paciente falasse a língua do país e que mesmo com intérpretes a comunicação é difícil, mas também trazem que não importa se a paciente sabe ou não a língua, que a enfermeira deve prestar um bom cuidado e adaptar suas formas de comunicação.…”
Section: As Dificuldades Encontradas Na Assistência àS Mulheres Imigrunclassified
See 1 more Smart Citation